Innovation nudging—A novel approach to foster innovation engagement in an incumbent company - Maximilian Stieler; Tassilo Henike (Creativity and Innovation Management, 2021)
Engaging employees to contribute to corporate innovation is vital for the future success of companies. In particular, incumbent companies face severe barriers in involving employees from various organizational locations. Long-term employments, highly specified organizational units, and hierarchical management structures are designed to preserve the status quo rather than promoting transformational changes. Thus, such companies often struggle with engaging their employees constantly and breaking down three kinds of innovation barriers: limited meaning, allowance, and/or capability. In this paper, we present innovation nudging as a novel approach, aiming to overcome the limitations of traditional corporate innovation management approaches. Such approaches largely pretend how employees should behave. Since such approaches are not part of employees' common behaviour, prior research has well explored the limits of such approaches. In contrast, nudging addresses subtly persons' cognition by presenting rewarding behaviour options in a way that individuals can easily deal with. Based on a 3-year observation of the introduction of innovation nudging at a leading German manufacturer of pumps, our results answer how different nudging types can be systematically used to create innovation engagement and to propel transformations in incumbent companies. Practical implications as well as avenues for future research are discussed.
Keywords: 330; corporate transformation; digitalization; foresight; ideation; innovation management; innovation tools; nudging